Hsp27 expression and ratio between cell proliferation rate and apoptosis in breast cancer with and without axillary metastases - Clarice M. Feyh Birnfeld; Vinicius D. Silva (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: The involvement of the immune system in the process of neoplasms has been increasingly studied due to its potential in antitumor therapy. Objectives: To evaluate the expression of heat shock protein 27 (Hsp27) in tissue samples from invasive ductal carcinomas with and without the presence of axillary sentinel lymph node metastasis, as well as to study the relationship of cell proliferation rate (Ki-76) and apoptosis (caspase 3) compared with samples of fibrocystic change in breast tissue. Methods: Cross-sectional study with tissue samples collected at the Hospital São Lucas, between September 2001 and October 2009, divided into three groups: 1. fibrocystic breast change (control group); 2. invasive ductal carcinoma of the breast with presence of lymph node metastasis; and 3. absence of lymph node metastasis. Results: Increased Hsp27 expression was observed in the group of non-metastasis carcinomas when compared to the other groups. There was difference in Ki-67 protein expression and in the ratio between cell proliferation and apoptosis among the carcinoma groups compared to the control group. However, there was no significant difference between the carcinoma groups or between the expressions of caspase 3 in the three groups, when compared to each other. Conclusion: Quantitative analysis of Hsp27 demonstrated increased protein expression in primary neoplasm tissues and in lymph nodes in carcinomas without axillary sentinel lymph node metastasis. Although the methodology and the number of cases do not allow concluding that this behavior in metastatic disease is a constant finding, this justifies the need to evaluate this finding in future studies.